Synergetic Learning Model: The Sum is Greater - Kevin Thompson (Adult Education Research Conference, 2016)
Scholars study a variety of factors that improve adult education outcomes. Academic research is typically focused on a single factor. There is a lack of guidance on combining research findings to create synergy. The opportunity exists to create a synergetic learning model that combines the work of many scholars.
Keywords: Learning; Model; Application; Synergy